2020
DOI: 10.3390/atmos12010014
|View full text |Cite
|
Sign up to set email alerts
|

Observing System Simulation Experiment to Reproduce Kelvin Wave in the Venus Atmosphere

Abstract: Planetary-scale 4-day Kelvin-type waves at the cloud top of the Venus atmosphere have been reported from the 1980s, and their significance for atmospheric dynamics has been pointed out. However, these waves have not been reproduced in Venus atmospheric general circulation models (VGCMs). Recently, horizontal winds associated with the planetary-scale waves at the cloud top have been obtained from cloud images taken by cameras onboard Venus orbiters, which could enable us to clarify the structure and roles of Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this study, we mainly focused on the thermal tide in the analysis for just one period. In the previous data assimilation test studies, it has been reported that the cold collar 49 and planetary-scale Kelvin waves 50 , 51 could be reproduced with sufficiently frequent observations. We are now planning to produce analyses with a number of observation periods, with which such kind of short period disturbances can be reproduced and investigated widely in the Venus research community.…”
Section: Resultsmentioning
confidence: 92%
“…In this study, we mainly focused on the thermal tide in the analysis for just one period. In the previous data assimilation test studies, it has been reported that the cold collar 49 and planetary-scale Kelvin waves 50 , 51 could be reproduced with sufficiently frequent observations. We are now planning to produce analyses with a number of observation periods, with which such kind of short period disturbances can be reproduced and investigated widely in the Venus research community.…”
Section: Resultsmentioning
confidence: 92%
“…They indicated that the cold collar is successfully reproduced by assimilating at least 2 or 3 vertical temperature profiles in the polar region every 4 or 6 hr. Recently, Sugimoto et al (2021) assimilated the horizontal wind associated with equatorial Kelvin-type waves which was artificially forced in the Venus GCM of Yamamoto and Takahashi (2012). As a result, they found that 4-day planetary-scale Kelvin-type waves could be reproduced when the horizontal wind in low-latitudes was assimilated every 6 hr at 70 km altitude.…”
Section: 1029/2022je007689mentioning
confidence: 99%